Breeding of ‘DND358’: A new soybean cultivar for processing soy protein isolate with a hypocholesterolemic effect similar to that of fenofibrate - Bo Song; Zhendong Qiu; Mingxue Li; Tingting Luo; Qi Wu; Hari B. Krishnan; Junjiang Wu; Pengfei Xu; Shuzhen Zhang; Shanshan Liu (Journal of Functional Foods, 2022)
Soy proteins have hypocholesterolemic effects (HCE). Here, we developed a soybean cultivar ‘DND358’, which is superior for processing hypocholesterolemic soy protein isolate beverage powder (DND358-SPI). ‘DND358’ carries four recessive null alleles for the α subunit of 7S globulin and the G1, G2, and G4 subunits of 11S globulin (tetra null), was selected from a population derived from a three-way cross. The tetra null mutation resulted in a compensatory increase in the α′ subunit level and arginine content. The oral administration (300 mg/kg/day) of DND358-SPI processed from ‘DND358’ significantly decreased the fatty liver symptoms and hepatic lipid accumulation; reduced the hepatic total cholesterol (TC), triacylglycerol (TG) levels and atherogenic index (AI) value, in rats fed a high-cholesterol diet. Conversely, DND358-SPI administration markedly elevated high-density lipoprotein cholesterol levels, to values significantly higher to those fed on fenofibrate (FF, 30 mg/kg/day), a hypocholesterolemic drug. The HCE of DND358-SPI were similar to that of FF.